Analisis Strategi Pedagang Konvensional dalam era Modernisasi (Studi Kasus Pasar Royal Kota Serang) - Qodri, Ilham Fauzul; Tesniyadi, Dema (Lembaga Yasin AlSys, 2022)
This study aims to determine the impact of modernization on conventional traders at Pasar Royal Serang City and this study is also to determine the strategy of conventional traders to survive in the midst of the modernization era. This research method uses descriptive qualitative research methods, in the process of collecting data the researchers made direct observations to the place then the researchers also interviewed several informants in order to obtain definite information. The results of this study describe that the modernization that occurs has an impact on conventional traders in the Royal Market, Serang City, especially in decreasing income due to changes in shopping patterns made by consumers.